Triumph and Solidarity: BC Communists in the Early Years of the Great Depression - Bartlett, Jon (AU Press, 2025)
British Columbia was the site of some of the most significant events in the history of the labour movement and had some of the best-organized and most politically conscious communist workers. In this illuminating volume, Jon Bartlett follows the activities of BC Communists from the onset of the Great Depression to the coming of the Popular Front and investigates the collisions between these Communists and the organs of the federal, provincial, and municipal governments. Reflecting on the vectors of cultural resistance, from the creation of vernacular newspapers to the circulation of popular song and verse, Bartlett charts workers’ efforts to resist wage cutbacks in mines, mills, and the logging and fishing industries and describes the organization of opposition to the relief camps and its outcomes. – Publisher's description
OCLC: 1373833201
Keywords: British Columbia Economic conditions 20th century; Communists British Columbia History 20th century; Grèves et lock-out Colombie-Britannique Histoire 20e siècle; HISTORY / Canada / Provincial; Territorial & Local / British Columbia (BC); Labor movement British Columbia History 20th century; Mouvement ouvrier Colombie-Britannique Histoire 20e siècle; Strikes and lockouts British Columbia History 20th century; Travailleurs Colombie-Britannique Histoire 20e siècle; Working class British Columbia History 20th century

The Making of a Radical Immigrant - Caccia, Ivana (Friesen Press, 2025)
The radical immigrant in the title of this book, Edo Jardas, was a young Croatian who arrived in Canada in May 1926 and worked for several years as a lumberjack in the hinterland of British Columbia. He was a loyal member of the Communist Party of Canada, a newspaper editor, and a militant trade union activist in the Canadian Croatian community. He fought in the Spanish Civil War in 1937 and returned to Canada as a war veteran. Jardas left Canada for Yugoslavia in 1948 where he assumed several prominent political functions, including the post of mayor of the largest harbour in the country-his hometown of Rijeka-from 1952 to 1955. Rather than being a simple biography, this book describes the circumstances that shaped the Croatian immigrant community in the hostile social and natural environment of Canada. The community was deeply engaged in the political debates concerning the Croatian status in the Kingdom of Serbs, Croats, and Slovenes (later renamed as Yugoslavia) since its foundation in 1919. The question of national identity and its affirmation at home and in the diaspora therefore figured pre-eminently in the Croatian immigrant press.The book is also very much a study in Canadian history. It is an account of the political radicalization of the Canadian working class, inspired by the international communist movement at a time of major economic and political upheaval in the post-WWI decades. –Publisher's description

35 Accords: Re-Imagining British Columbia's Public Sector Labour Relations - Calvert, John; Penikett, Tony (Ethics Press, 2025)
What does a cash-strapped government do when the collective agreements for almost a quarter million of its unionized employees expire simultaneously while wishing to maintain a respectful relationship with its labour supporters? In 1997, the Premier of British Columbia (BC), Canada, Glen Clark, thought of an imaginative solution. It was to offer unions an opportunity to participate with the government in developing policies on issues affecting their members and the services they provide. This was BC’s public sector policy Accord process. The goal was to establish a different, more collaborative relationship with unions, one in which they had a voice in shaping policy solutions. This parallel process – entirely separate from collective bargaining - would also avoid the adversarial relationship that so often characterizes a government’s relations with its unions, by recognizing the positive role unions and their members could play in contributing to improving BC’s public programs and services. The authors, who worked on the Accord process with Premier Clark, provide an insider’s story of the intensive three-year period, during which the parties negotiated 35 policy accords across the entire provincial public sector. The Accords covered a wide range of issues, including pension trusteeship and portability, early retirement, provincial school class size, benefits trusts, government procurement policy, hospital laboratory services, workforce training, pay equity, creation of a health and safety agency and numerous smaller policy fixes. The accord process demonstrated that it was possible for a government to initiate a new and more collaborative relationship with its unions by inviting them into the policy process. The accords definitely improved relations with the government and contributed to collective bargaining settlements within the government’s money mandate. –Publisher's description

Cold War Workers: Labour, Family, and Community in a Nuclear State - Campbell, Isabel (McGill-Queen’s University Press, 2025)
As Canada sought to protect its borders and aid its allies during the Cold War, many people were recruited to build the emerging security state: as construction and maintenance workers, engineers, members of the armed forces, medical researchers, and research subjects. Security work transformed the lives of individuals, families, and communities in ways that were both predictable and surprising, and both beneficial and harmful; the militarization and colonization of Indigenous lives and lands was especially disruptive. The opening essays of Cold War Workers intimately portray the complicated effects of Cold War labour upon Indigenous lives. Elmer Sinclair, a residential school survivor and member of the Canadian armed forces, achieved equality with white men through his militarized masculinity. His more positive professional experience contrasts with those of Indigenous workers on northern radar lines, many of whom lost languages, connections to the land, and other elements of traditional cultures as they sought new skills and better employment. Diverse Indigenous experiences of Cold War security work set the scene for the second set of essays, which explore the impact of security preoccupations on marginalized groups – the study of extreme isolation through scientific experimentation on human subjects; the targeting of gay men with psychiatric labelling to enforce an idealized masculinity; and the restriction of gender mobility in the Canadian military, and the pushback from servicewomen. Cold War Workers raises questions about the influence of settler-colonial masculine institutional values on those who laboured for the Cold War state and society. By comparing the experiences of different types of workers, families, and communities, this volume reveals how race, gender, and privilege affected people in varied and sometimes unexpected ways. – Publisher's description
OCLC: 1460941575
Keywords: Cold War Social aspects Canada; Cold War War work Canada; Guerre froide Aspect social Canada; Guerre froide Participation des civils Canada

Leading from the Heart: The Battles of a Feminist, Union Leader and Politician - Darcy, Judy (Douglas & McIntyre, 2025)
In this inspiring memoir, Judy Darcy recounts the remarkable turns that brought her from library worker to president of Canada’s largest labour union, and from there to groundbreaking legislator focused on many of our most pressing issues, including health care, the rights of immigrant workers and the toxic-drug crisis. As this rich memoir shows, the life of activist, union leader and legislator Judy Darcy mirrors many of the great social and political currents of the modern era. Opening in the charged atmosphere of the feminist movement in the late 1960s, when the twenty-year-old Darcy—swept up by the promise of historic, liberating change—infiltrates a beauty pageant and later disrupts Parliament over reproductive rights, the story then reaches back to her earliest years as the daughter of immigrants deeply scarred by World War II. In this tale of personal trauma and desire for justice, Darcy recounts the remarkable turns that brought her from library clerical worker to leading public figure. Her rise through the ranks of the country’s largest union—the Canadian Union of Public Employees, with several hundred thousand members—culminates in her 1991 election as national president, a traditionally male-dominated role. Years later, after moving from Ontario to British Columbia, she is elected to public office, becoming an NDP MLA. Here, as the only North American minister of mental health and addictions, she confronted the ravages of the toxic-drug crisis, working to help some of society’s most vulnerable. Throughout the tumultuous events of her career and personal life, Darcy is forever working for those on the margins, fighting to protect workers’ rights, water rights, health care, childcare and reproductive choice, and helping secure a landmark Supreme Court decision in favour of same-sex partner pensions. Powered by intense conviction and intimately personal experience, her candid story offers a vision of a new kind of leadership, steeped in compassion and able to negotiate the most urgent and complex challenges of our fractured era. – Publisher's description
OCLC: 1520331456
Keywords: Activistes Colombie-Britannique Biographies; Autobiographies; Darcy; Judy; Dirigeantes syndicales Colombie-Britannique Biographies; Dirigeants syndicaux Colombie-Britannique Biographies; Feminists British Columbia Biography; Femmes activistes Colombie-Britannique Biographies; Femmes politiques Colombie-Britannique Biographies; Féministes Colombie-Britannique Biographies; Labor leaders British Columbia Biography; Political activists British Columbia Biography; Politicians British Columbia Biography; Politiciens Colombie-Britannique Biographies; Women labor leaders British Columbia Biography; Women political activists British Columbia Biography; Women politicians British Columbia Biography

Seasonal Sociology - Davidson, Tonya K.; Park, Ondine (University of Toronto Press, 2025)
Life in Canada is shaped by the seasons – marked, celebrated, enjoyed, and sometimes dreaded in ways that respond directly to the changing cycles in nature. Sociological thinking encourages us to question the aspects of everyday life that we may otherwise take for granted. Seasonal Sociology takes a sociological approach to thinking about the seasons, providing a unique perspective for understanding social life. Each chapter in this collection explores key issues of sociological interest through the passage of time and seasonal change. The authors wield seasonality as a powerful tool that can bridge small-scale interpersonal interactions with large-scale institutional structures. This collection of contemporary Canadian case studies is wide-ranging and analyses topics such as pumpkin spice lattes, policing in schools, law and colonialism, summer cottages, seasonal affective disorder, Vaisakhi celebrations, and more. The second edition introduces new chapters on Labour Day and organized labour, disability and online dating, maple sugar shacks, seasonal agricultural work, wildfires, and social movements like Pride and Black Lives Matter. Seasonal Sociology ultimately offers fresh, provocative ways of thinking about the nature of our collective lives. – Publisher's description
OCLC: 1484905875
Keywords: Canada Mœurs et coutumes; Canada Social life and customs; Case studies; Saisons Aspect social Canada; Saisons Canada; Seasons Canada; Seasons Social aspects Canada; Sociologie Canada Études de cas; Sociology Canada Case studies; Études de cas

Le Moulin-à-Fleur de Sudbury: quartier ouvrier, territoire canadien-français - Dupuis, Serge; Carrey, Normand (Les Presses de l'Université d'Ottawa : Centre de recherche sur les francophonies canadiennes, 2025)
À son apogée entre 1945 et 1975, le Moulin-à-Fleur ou la paroisse Saint-Jean-de-Brébeuf se vantait d'être le quartier francophone de Sudbury et de l'Ontario. Il représentait en effet la pierre angulaire pour les autres communautés francophones ainsi que le fondement de la vie culturelle, économique et politique des Franco-Ontariens. Mais l'histoire n'a jamais été racontée de façon détaillée. Des années de recherches approfondies ont incité les auteurs à se plonger dans de nombreux écrits, articles scientifiques, archives personnelles, articles de journaux et témoignages afin de livrer cette première étude globale. Divisé en deux volets qui se complètent, ce récit retrace à la fois l'héritage des familles qui se sont battues pour offrir un quotidien et un avenir brillants à leur descendance et la lutte féroce menée par des pionniers, notamment Omer Thériault, Gaétan Gervais et Hélène Gravel, pour la défense culturelle et patrimoniale. Mais tous ces souvenirs dorment dans les rues de l'ancien quartier ou comme Mme Tregonning-Whissell le disait, "à l'ombre des silos". Ce livre témoigne des origines d'une communauté marquée par le dur labeur des mineurs de l'International Nickel, tout en évoquant le rôle des enseignants qui éveillaient les jeunes générations à un monde de possibilités. Le Moulin-à-Fleur de Sudbury rend hommage aux valeurs de charité et d'entraide qu'incarnait ce quartier qui célèbre au-delà de 120 ans de vie communautaire et culturelle. – Résumé de l'éditeur
https://muse.jhu.edu/book/136092/pdf/download OCLC: 1504742532
Keywords: Canadiens français Ontario Grand Sudbury Histoire; Grand Sudbury (Ont.) Histoire; Moulin-à-Fleur (Grand Sudbury; Ont.) Histoire; Neighborhoods Ontario Greater Sudbury History; Quartiers (Urbanisme) Ontario Grand Sudbury Histoire

Industrial Relations in Canada - Foster, Jason; McQuarrie, Fiona A. E. (Wiley, 2025)
Industrial Relations in Canada, Fifth Edition, offers students a comprehensive and accessible introduction to the Canadian industrial relations system. Designed for learners with minimal knowledge of the subject, this market-leading textbook blends theory, practice, and process in a clear and engaging way. Student-friendly chapters walk through key topics such as unionization, collective bargaining, dispute resolution, and evolving legal frameworks, while minimizing jargon and legalistic language. Throughout the book, timely coverage of controversial and complex issues fosters critical thinking and real-world problem-solving skills. Integrating a process-oriented approach developed through years of classroom experience, Industrial Relations in Canada, Fifth Edition, is ideal for university and college students in introductory labour relations courses, as well as adult learners in business, human resource management, and labour studies programs. With its strong foundation in both academic theory and practical application, it is also an excellent springboard for more advanced studies in industrial relations. New to this edition: new chapter-opening vignettes featuring Canadian labour relations practitioners; new discussions of social media’s role in union organizing and labour activism, and the effects of technological change on labour-management dynamics; new coverage of current research on union and workplace issues; updated news stories in every chapter reflecting current events in Canadian workplaces; discussions of the impacts of COVID-19 and climate change on labour relations; enhanced analysis of recent court decisions affecting collective bargaining; and updated statistics and demographic data on unionization, strikes, and lockouts across Canada. –Publisher's description

Constructing Modern Slavery: Law, Capitalism, and Unfree Labour - Fudge, Judy (Cambridge University Press, 2025)
Modern slavery laws are a response to global capitalism, which undermines the distinction between free and unfree labour and poses intense challenges to state sovereignty. Instead of being a solution, Constructing Modern Slavery argues that modern slavery laws divert attention from the underlying structures and processes that generate exploitation. Focusing on unfree labour associated with international immigration and global supply chains, it provides a novel socio-legal genealogy of the concept 'modern slavery' through a series of linked case studies of influential actors associated with key legal instruments: the United Nations, the United States, the International Labour Organization, the European Union, the United Kingdom, and Walk Free Foundation. Constructing Modern Slavery demonstrates that despite the best efforts of academics, advocates, and policymakers to develop a truly multifaceted approach to modern slavery, it is difficult to uncouple antislavery initiatives from the conservative moral and economic agendas with which they are aligned. –Publisher's description

Public Service in Tough Times: Working Under Austerity in Manitoba - Hajer, Jesse; Hudson, Ian; Keith, Jennifer (University of Manitoba Press, 2025)
In 2016, Brian Pallister's Progressive Conservative Party of Manitoba successfully campaigned on a platform to reduce taxes and restore the balance between revenue and spending. The years that followed their victory saw wages frozen, emergency rooms closed, intensive care unit beds reduced, healthcare jobs eliminated, Manitoba Housing funding slashed, and payments to foster parents decreased, as the civil service was diminished by 27 percent. Public Service in Tough Times gives voice to the people behind the balance sheets, shedding light on the vicious cycle of understaffing, burnout, attrition, and despair created by austerity policy. Using survey data from thousands of public sector workers and carefully compiled statistics on spending and staffing, editors Jesse Hajer, Ian Hudson, and Jennifer Keith, demonstrate how cuts to government expenditures disproportionately benefit the wealthy and exacerbate poverty and inequality. As the virtues of small government, tax cuts, and private sector investment continue to be the rallying cry of right-leaning politicians worldwide, this impeccably researched case study delivers a crushing critique of austerity and its consequences. –Publisher's description

The Left in Power: Bob Rae's NDP and the Working Class - High, Steven C. (Between the Lines, 2025)
At the end of the twentieth century, as social democratic parties around the world struggled to produce a coherent response to the deindustrialization crisis, many pivoted towards progressive neoliberalism and Third Way social democracy. Almost everywhere, they turned their backs on the weakened trade union movement and embraced neoliberal assumptions about labour force flexibility and global competition. Shamefully, Third Way social democrats emphasized the moral dimension of poverty rather than its structural causes as they abandoned the old redistributive class politics of the Left. Based on extensive archival research and interviews with NDP politicians, senior economic policy advisors, and trade unionists, The Left in Power examines the response of the political Left in Ontario to the crisis that gripped the old ‘industrialized world.’ Steven High revisits the heartbreaking years of Bob Rae’s Ontario NDP government—from their historic and unexpected 1990 victory, to their policy shifts that left working-class voters feeling betrayed, to their landslide defeat in 1995—to uncover what we can learn from one social democratic party’s mistakes about how to govern from the Left. –Publisher's description
OCLC: 1461919686
Keywords: New Democratic Party of Ontario; Ontario Economic conditions 1991-; Ontario Politics and government 1990-1995; Rae; Bob

Work and Labour in Canada: Critical Issues - Jackson, Andrew; Thomas, Mark P.; King, Adam D. K. (Canadian Scholars Press, 2025)
Over the last several decades, the workplace in Canada has experienced profound changes. Work has become increasingly insecure for a growing number of workers, and income inequality has deepened. New technologies have reshaped labour processes and have enhanced elements of employer control over work and workers. Entry into the labour market is itself a difficult process, as young workers struggle to match qualifications and credentials with jobs, while for many older workers, retirement with a secure income is a diminishing prospect. The demographic composition of the labour market is transforming, yet this change is conditioned by longstanding patterns of inequality in terms of gender, race, disability, and immigration status. Work and Labour in Canada explores the changing world of work, mapping out major trends and patterns that define working life and identifying the economic, social, and political factors that shape the contemporary workplace. Evaluating working conditions and the quality of jobs from a critical perspective, this text presents an analysis of recent trends in employment and unemployment as well as outlines the role and impact of unions and other workers’ organizations. The fourth edition includes a new chapter on work and technology, updated statistical data, and additional content on the basic income debate, labour and climate change, and COVID-19. This thoroughly revised and updated edition is essential for teachers, researchers, labour activists, and students of labour studies, sociology, political science, political economy, and economic geography programs. –Publisher's description

The Art of Solidarity: Labour Arts and Heritage in Canada - Kristofferson, Robert B.; Ross, Stephanie (Between the Lines, 2025)
The Art of Solidarity delves into the rich tapestry of labour arts and heritage in Canada—from protest music and union banners, to murals, community theatre, and oral histories, to workers’ history museums and arts festivals—showcasing how these expressions of working people’s culture have been essential to challenging inequality and fostering solidarity. This inspiring collection highlights the resilience and creativity of labour arts and heritage practitioners who, despite financial and organizational challenges, continue to amplify the voices and experiences of working-class communities. In an economy characterized by growing polarization, inequality, precarity, and uncertainty about the future and meaning of work, labour arts and heritage has a central role to play in providing answers that challenge the prevailing narratives about whose work matters and whose efforts are central to our communities’ wellbeing. This work is more important than ever before. – Publisher's description
OCLC: 1515688714
Keywords: Arts Aspect politique Canada; Arts Political aspects Canada; Arts and society Canada; Arts et société Canada; Arts; Canadian; Labor in art; Labor movement Canada; Labor movement in art; Mouvement ouvrier Canada; Mouvement ouvrier dans l'art; Political art Canada; Solidarity Canada; Solidarity Political aspects Canada; Travail dans l'art

Women United: Stories of Women's Struggles for Equality in the Canadian Auto Workers Union - Nash, Peggy; White, Julie (Between the Lines, 2025)
Based on the firsthand stories of dozens of women leaders in the Canadian Auto Workers (CAW), Women United examines what workplaces were like for women, how they became involved in the union, and the challenges women faced, sometimes at great personal cost. From struggles for representation in their union to their fight for affirmative action and childcare, and work against gender-based violence and harassment, Peggy Nash and Julie White show how these feminist activists were joined in struggle not only by their union sisters, but also by their sisters from the broader women’s movement, who learned from them about the importance of women’s workplace rights. Nash and White document the decades-long struggles of generations of women activists in the CAW, who, despite their few numbers, managed to build a better, more inclusive union. A testament to the union’s motto that "fighting back makes a difference," Women United makes an important contribution to feminist, labour, and social history. – Publisher's description
OCLC: 1526712168
Keywords: BIOGRAPHY & AUTOBIOGRAPHY; CAW-Canada History; Electronic books; Femmes dans le mouvement ouvrier Canada Histoire; Labor movement Canada History; Labor union members Canada History; Mouvement ouvrier Canada Histoire; POLITICAL SCIENCE; Syndiqués Canada Histoire; Women; Women in Politics; Women in the labor movement Canada History; Women labor union members Canada History

Rethinking Feminist History and Theory: Essays on Gender, Class, and Labour - Pasolli, Lisa; Smith, Julia (University of Toronto Press, 2025)
Rethinking Feminist History and Theory considers the past, present, and future of feminist history and theory, emphasizing how feminism has influenced the histories of gender, class, and labour, and their intersections. This vibrant collection, inspired by the work of historian and women’s studies scholar Joan Sangster, features essays from academics across multiple disciplines, highlighting the dynamism of feminist historical scholarship in Canada. The book explores questions such as: How has women’s resistance and radicalism been expressed, lived, represented, and repressed over the past century? How do we research these phenomena? How do we situate feminism in relation to other movements for egalitarian social change? Contributors explicitly address these recurring themes, aiming to chart new directions for future research and teaching. While primarily Canadian-focused, the collection includes global perspectives, with contributions from scholars in Chile, Finland, Sweden, and the UK. These essays emphasize the importance of cross-disciplinary collaboration, incorporating insights from labour studies, political economy, anthropology, legal studies, and feminist theory. Ultimately, Rethinking Feminist History and Theory engages deeply with Sangster’s rich and wide-ranging work to understand and interpret women’s experiences. It seeks to inspire future scholarship and teaching in feminist history and theory, showcasing the ongoing relevance and adaptability of feminist perspectives. – Publisher's description
OCLC: 1445896471
Keywords: Feminism Canada History; Feminist theory Canada History; Femmes Activité politique; Femmes Conditions sociales; Féminisme Canada Histoire; Théorie féministe Canada Histoire; Women Legal status; laws; etc; Women Political activity; Women Social conditions

Policing in Canada: Concepts, Actors and Challenges - Prado, Grégory Gómez del; Leman-Langlois, Stéphane (Éditions JFD, 2025)
Drawing on both the academic field and homeland security practices, this book addresses the essential themes in the study of policing: its origin, theorization and structure. It focuses on the public police in Canada, making it a unique and original perspective. It adopts a critical approach to the fundamental aspects of policing, including patrol, investigation, intelligence, private policing, and transnational policing. It also highlights the issues of legitimacy and image management, as well as the contemporary challenges organizations and individuals face. Reflecting the authors’ background, this book brings a criminological perspective to the study of Canadian policing while remaining rooted in its day-to-day practice. As such, it will appeal to those interested in the workings of traditional policing and those wishing to explore the more complex aspects of policing in society.

Standing Up to Big Nickel: The Story of the Mine, Mill and Smelter Workers Strike, 1958 - Quinlan, Elizabeth (McGill-Queen's University Press, 2025)
All miners and smelter workers know the folly of going on strike when their employer holds a stockpile. In 1958 the International Nickel Company had enough nickel on hand to guarantee sales for at least six months. Despite this, fourteen thousand miners and smeltermen in Sudbury, Ontario, downed their tools and struck against the corporate titan of the mining industry. Standing Up to Big Nickel is a comprehensive portrait of a pivotal strike by the International Union of Mine, Mill, and Smelter Workers, a union that has inspired exceptional levels of solidarity among its members. The Cold War and the resulting instabilities in the Canadian labour movement form the backdrop to Elizabeth Quinlan’s engrossing analysis. The union straddled the line, she shows, between its historical commitment to working-class struggle and the newly restrictive legal landscape of the postwar era. Retrospective accounts by surviving union members, leaders, family, and community members bring to life the history of a distinctive group of workers who sweated over smelter furnaces and toiled underground in perilous conditions. Quinlan traces the events before, during, and after one of Canada’s greatest strikes in both magnitude and duration. Featuring biographical sketches and scenes based on archival and documentary data, Standing Up to Big Nickel captures an intensely dramatic juncture in Canadian labour history. –Publisher's description

Social Determinants of Health: Canadian Perspectives - Raphael, Dennis (Canadian Scholars' Press, 2025)
Now in its fourth edition, Dennis Raphael’s Social Determinants of Health offers the definitive Canadian discussion of the primary factors that influence the health of Canada’s population.This unique text on the social determinants of health contains contributions from top academics and high-profile experts from across Canada. Taking a public policy approach, the contributors to this edited collection critically analyze the structural inequalities embedded in our society and the socio-economic factors that affect health―including income, education, employment, housing, food security, gender, and race. This new edition includes recent statistics, new developments in early childhood education and the implementation of Canada’s national childcare system, and new content on the social determinants of Indigenous Peoples’ health. Particular attention is paid to how economic globalization and the acceptance of neoliberal governing ideology is shaping the health of Canadians. The COVID-19 epidemic vividly illustrated the importance of the social determinants of health, as sickness and death rates were strikingly higher among Canadians in groups already experiencing adverse living and working conditions and poorer health: lower income Canadians, recent immigrants of colour, and those experiencing housing and food insecurity. If anything positive is to come out of this experience, it will be recognition that in the current post-COVID-19 environment, it is essential to understand the socio-economic conditions that shape the health of individuals and communities. Social Determinants of Health, Fourth Edition is aimed at courses focusing on the social determinants of health at Canadian universities and colleges, particularly those in health studies and nursing, but also allied health, sociology, and human services. –Publisher's description
OCLC: 1450214834

The Price of Gold: Mining, Pollution, and Resistance in Yellowknife - Sandlos, John; Keeling, Arn (McGill-Queen’s University Press, 2025)
Fifty years of gold mining at Yellowknife in the Northwest Territories spurred northern settlement and produced millions of dollars in profits. But mineral processing also had catastrophic environmental effects and left a troubled legacy. When two mining companies in Yellowknife began processing gold ore in the 1940s, they did so with little or no pollution controls. Giant Mine spewed thousands of kilograms of arsenic trioxide from its roaster stack into the environment, causing illness and death among people and animals, especially in the adjacent Yellowknives Dene community. Even after the companies installed controls, arsenic trioxide continued to enter the atmosphere and waterways. Eventually Giant Mine, the biggest polluter, would deposit the arsenic dust beneath the mine, leaving 237,000 tonnes of highly toxic material buried underground. For decades, the mining companies and the federal government hid the worst effects of the pollution, doubted their own studies, and resisted calls for action. Yet the Yellowknives Dene fought back with the support of labour unions and environmental groups, questioning the safety of the air and water in their community and the massive toxic deposit underground. The Price of Gold traces the troubling history of one of Canada’s most contaminated sites but also the inspiring story of Indigenous, labour, and environmental activists who resisted the ongoing poisoning of their communities. – Publisher's description
OCLC: 1502656834
Keywords: Arsenic trioxide Health aspects Northwest Territories Yellowknife; Dene Social conditions Northwest Territories Yellowknife; Environmental protection Northwest Territories Yellowknife; Environnement Protection Territoires du Nord-Ouest Yellowknife; Giant Mine (Yellowknife; N.W.T.); Gold mines and mining Environmental aspects Northwest Territories Yellowknife; Gold mines and mining Government policy Northwest Territories Yellowknife; Gold mines and mining Health aspects Northwest Territories Yellowknife; Or Mines et extraction Aspect de l'environnement Territoires du Nord-Ouest Yellowknife; Or Mines et extraction Politique gouvernementale Territoires du Nord-Ouest Yellowknife; Yellowknife (N.W.T.) Environmental conditions

The New Politics of Western Canada: Contested Histories, Uncertain Futures - Smith, Charles W.; McIntosh, Thomas A. (UBC Press, 2025)
The Canadian West: an economic engine with a history of grievance against federal power emanating from the east. The New Politics of Western Canada grapples with the West’s complex, multifaceted past to promote a better understanding of this vast region’s political realities and the challenges that lie ahead. Contributors re-examine the historical and contemporary meanings attached to “the West” as a form of identity, through themes such as colonialism, gender, and class. They develop a nuanced analysis of Western political ideology, from resentment-based populism to the regional left. And they explore pressing Western economic and policy concerns, such as labour, health care, and Indigenous democratic participation and protest. Together, these themes provide intelligent new ways of interpreting underexplored aspects of Western Canadian politics, adding depth to earlier attempts to explain the region as a political, economic, or sociological space. – Publisher's description
OCLC: 1523057766
Keywords: Canada; Western Politics and government

Young and Female: International Perspectives on the Future of Farming - Srinivasan, Sharada; Pan, Lu; Ambarwati, Aprilia (Practical Action Publishing, 2025)
Women’s roles in sustaining and the revival of farming are indispensable. Based on research in Canada, China, India and Indonesia, the book offers a global perspective on young women’s pathways into farming. It responds directly to concerns about the generational sustainability of smallholder farming worldwide. Despite their crucial contribution to the reproduction of farming and its belated recognition in policy discourse, women farmers continue to face constraints in access to agrarian resources and services, and recognition as farmers in their own right. –Publisher's description
/https://www.akatiga.org/wp-content/uploads/2025/06/Young-and-Female_International-Perspectives-on-the-Future-of-Farming.pdf

A Labour of Love: In Pursuit of Just Causes - Stewart, Herman (Independently published, 2025)
From a small rural village in Jamaica to the negotiating tables of Canada’s labour movement, A Labour of Love traces the extraordinary journey of Herman Stewart, a community builder, labour activist, and relentless advocate for justice.This deeply personal memoir captures the heart of a man who arrived in Canada with modest beginnings and rose to become a respected leader in the Jamaican Canadian community and the broader labour movement. Through vivid storytelling, Stewart recounts his early life in Jamaica, the cultural challenges of immigration, and his unyielding commitment to workers’ rights and social justice.With wisdom, humour, and humility, Stewart sheds light on the struggles and triumphs of a generation that paved the way for change in Canadian society. His story is not only a tribute to activism and perseverance but also a call to action for future generations to carry forward the fight for equity and inclusion.This is more than a memoir; it’s a legacy of purpose, courage, and hope. –Publisher's description

Workers of War and Empire from New France to British America, 1688–1783 - Tomczak, Richard H. (McGill-Queen’s University Press, 2025)
Throughout the eighteenth century, the French and British empires mobilized thousands of labourers in Canada through a system of mandatory labour known as “corvée.” This social arrangement was rooted in the feudal obligations of French peasants to landowners. Under the French regime, corvée was a custom, an obligation, and a form of obedience, a “local affair” embedded in an agricultural way of life that retainined a sense of reciprocity with mechanisms to discourage exploitation. However, with the British conquest of Quebec in 1763, and, later, the American Revolution, the corvée system assumed new dimensions. The British recognized the need for labour power in an underpopulated region and coopted the corvée customs for their own imperial ends. Though British officials retained some French statutes, they enacted new laws mobilizing the male inhabitants of New France to work in state enterprises (such as iron mining and logging), with Labourers holding little to no input into how the colonial state viewed their well-being. Leaning heavily on corvée as a form of conscription, the British army’s surging demand for workers in Quebec precipitated wide-spread protests. This crisis forced the royally appointed governor Frederick Haldimand to ratify a new provincial code regulating the use of corvée. Workers of War and Empire from New France to British America, 1688-1783 chronicles the transformation of the corvée system over a century, positioning French Canadian workers at the center of the narrative. – Publisher's description
OCLC: 1439102084
Keywords: Corvée Canada Histoire 17e siècle; Corvée Canada Histoire 18e siècle; Corvée Canada History 17th century; Corvée Canada History 18th century; French-Canadians History 17th century; French-Canadians History 18th century; Labor Canada History 17th century; Labor Canada History 18th century; Travail Canada Histoire 17e siècle; Travail Canada Histoire 18e siècle

Asian Canada Is Burning: Theories, Methods, Pedagogies, and Praxes - Torres, Rose Ann; Liujia Tian, Ian; Chau, Coly (Brill, 2025)
This book is an invitation to trouble the mobilization of “anti-Asian hate” in the aftermath of COVID-19 pandemic. Bringing together activists, organizers, academic, and artists, this book explores the historical and contemporary conditions that make theorizing “Asian Canadian” feasible. Grounded in a transnational queer and feminist lens, this book also aims to envision possible futures and solidarities. Ultimately, this collection is concerned with moments and places of tensions, confrontations, relations, and solidarity. We offer stories of insurgent encounters as people who identify as “Asian” navigate and implicate settler colonial nation-state to make new dreams, histories and intimacies. – Publisher's description
OCLC: 1466951245
Keywords: Asians Canada Social conditions; Asians Race identity Canada; Canada Conditions sociales; Canada Race relations; Canada Social conditions; Communautés de minorités sexuelles Canada; Group identity Canada; Identité collective Canada; Racism Canada; Racisme Canada; Sexual minority community Canada

Migrant Work by Another Name: Differential Inclusion and Precarity in Canada’s International Mobility Program - Vosko, Leah F. (University of Toronto Press, 2025)
Migrant Work by Another Name explores the complexities of Canada's evolving international migration and employment policy landscape. It critically examines the shift towards “mobility” programs under the recently inaugurated International Mobility Program (IMP). This shift occurs alongside the contraction of certain streams within Canada’s long-standing Temporary Foreign Worker Program (TFWP). The book investigates the implications of policy changes, influenced at once by public outcry over migrant worker exploitation and persistent demands for labour in the face of qualitative labour shortages in high-income countries like Canada. Grounded in a decolonial feminist political economy approach, Leah F. Vosko employs a mixed methods analysis to contrast the narrative of “mobility” with the persistent realities of precarity among transnational workers. The book features in-depth case studies of the three largest IMP subprograms – Working Holiday, Post-Graduation, and Spousal Work Permit programs – revealing how these initiatives, despite being touted as promoting mobility, provide for temporary migrant work by another name and perpetuate distinct forms of precarity. This critical perspective challenges the notion of progress in contemporary migration policies, shedding light on the ongoing challenges faced by transnational workers in Canada. – Publisher's description
OCLC: 1482258960
Keywords: Foreign workers Employment Government policy Canada Evaluation; International Mobility Program (Canada) Evaluation; Labor mobility Government policy Canada Evaluation; Main-d'œuvre Mobilité Politique gouvernementale Canada Évaluation